Cardiopulmonary complications in a patient with bezoar - Viveiros, Eulália (BMJ Publishing Group, 2013)
We report a case of a 17-year-old institutionalised male with a medical history of fragile X syndrome, bilateral congenital glaucoma, cataracts and pica disorder. He was transferred to our paediatric intensive care unit owing to respiratory failure and hypotension. On transoesophageal echocardiogram, he presented left atrium compression. A CT of the thorax and mediastinum revealed an unknown heterogeneous material in the lumen of the stomach and oesophagus, with a lung parenchyma suggestive of alveolar foreign material. Endoscopic evaluation showed diaper fragments inside the oesophagus and stomach. Fragmentation and suction of diaper material was made. Medical treatment was performed with inotropic support, conventional mechanical ventilation and antibiotics.